Decade of decision - Population Action International; Maguire/Reeder, Ltd. (Oley, PA : Bullfrog Films, 1994)
A film which examines the problem of an ever increasing world population and the resultant impact upon the natural environment. If the rate of population growth remains unchecked a major environmental disaster is inevitable. To forestall such an event, contraceptive education and materials, along with a reduction in wasteful consumption are suggested. This approach is considered inexpensive but would require political will and action
Copy in DVD Format
Narrated by Walter Cronkite
VHS Format
Keywords: Overpopulation -- Environmental aspects; Birth control